The lipid content of cisplatin- and doxorubicin-resistant MCF-7 human breast cancer cells - Todor, I.N.; Lukianova, N.Yu.; Chekhun, V.F. (Experimental Oncology, 2012)
Aim. To perform the comparative study both of qualitative and quantitative content of lipids in parental and drug resistant breast cancer cells. Materials and methods. Parental (MCF-7/S) and resistant to cisplatin (MCF-7/CP) and doxorubicin (MCF-7/Dox) human breast cancer cells were used in the study. Cholesterol, total lipids and phospholipids content were determined by means of thin-layer chromatography. Results. It was found that cholesterol as well as cholesterol ethers content are significantly higher but diacylglycerols, triacylglycerols content are significantly lower in resistant cell strains than in parental (sensitive) cells. Moreover the analysis of individual phospholipids showed the increase of sphingomyelin, phosphatidylserine, cardiolipin, phosphatidic acid and the decrease of phosphatidylethanolamine, phosphatidylcholine in MCF-7/CP and MCF-7/Dox cells. Conclusion. Obtained results allow to suggest that the lipid profile changes can mediate the modulation of membrane fluidity in drug resistant MCF-7 breast cancer cells.